Ejercicios anaeróbicos y su incidencia en el desarrollo de la fuerza muscular, de los aspirantes de la escuela de policías Cbos. Sócrates Arboleda Sanabria (Las Peñas) del cantón Babahoyo - Calderón Villafuerte, Jorge Pedro (2016)
THE RESEARCH WAS CARRIED ACAV POLICE SCHOOL CBOS. ARBOLEDA SOCRATES SANABRIA (LAS PEÑAS) CANTON BABAHOYO, ON THE THEME: ANAEROBIC EXERCISES AND ITS IMPACT ON THE DEVELOPMENT OF MUSCULAR STRENGTH, ASPIRING POLICE OFFICERS IN THIS WORK DIFFERENT PROCESSES WERE PERFORMED TO DESCRIBE THE PROBLEM THAT AROSE. FOR THE RESULTS OF RESEARCH A TREE PROBLEM IN RELATION TO THE NEGATIVE SITUATION OF THE ISSUES RAISED, IN WHICH THE CAUSES AND EFFECTS OF THE PHENOMENA WERE DETERMINED WAS ORGANIZED. AN EXTENSIVE LITERATURE SEARCH, INTERNET PAGES WHERE SUBSTANTIAL INFORMATION OF EXPERTS, WHICH HAS SERVED TO STRUCTURE THE THEORETICAL FRAMEWORK WAS FOUND WAS CONDUCTED. THE SURVEY WAS THEN APPLIED TO THE VARIOUS CANDIDATES AND COACHES, PLUS AN OBSERVATION GUIDE WAS APPLIED TO THE CONTROL PROCESSES WERE PERFORMED. AFTER PERFORMING THE PROCESSES ACHIEVING VERIFY THAT THE RESULTS SHOWN INDICATE THAT ASPIRING POLICE DO NOT PERFORM EXERCISES THAT HELP DEVELOP MUSCLE STRENGTH, THE EJERCICION THAT APPLY ARE NOT SUITABLE FOR SESARROLLEN YOUR BODY'S ABILITY TO HAVE BETTER IN A PROTECTION SO SELF AND SOCIETY